Speed control of DC motor using PID controller implementation with PLC - Muhammad Ezra-Ezwan, Mat Aris (2008)
The idea of motor speed control is to keep the rotation of the motor at the set speed. When used in speed applications, speed feedback control the DC motor’s speed or confirms that the motor is rotating at the desired speed. To maintain the speed, it requires the speed feedback at all times. The objective of this project is to use the algorithm of Proportional Integral Derivative (PID) controller to control the speed of the DC motor using Programmable Logic Controller (PLC) implementation. The used of PLC in this project will help to reduce complexity and easy to troubleshoot. The model of PLC which is used in this project is OMRON (CQM1H-CPU51) and the program for this controller system is in ladder diagram (CX programmer). The PID is implemented in the PLC program so that the system has a better response and less error. Finally, analysis of the response is made after the PID is implemented into the system.